Investigation of oscillation on certain dynamic equations - Hongxia Wang,; Qinghua Feng, (IJRDO -JOURNAL OF MATHEMATICS, 2019)
In this paper, some new oscillation criteria for a class of fractional dynamic equations with damping term on time scales are established by use of the properties of fractional calculus and generalized Riccati transformation technique, where the fractional derivative is defined in the sense of the conformable fractional derivative. Oscillation criteria for corresponding dynamic equations on time scales involving integer order derivative are special cases of the present results.